Trampoline In Physical Activity: Systematic Literature Review - Lina Meilani; Adi S (Indonesian Journal for Physical Education and Sport, 2025)
This study aims to analyze the use of trampolines as a form of physical activity, focusing on its health benefits, rehabilitation role, and potential risks. The method used was a systematic literature review (SLR) with a PRISMA approach, collecting and analyzing studies from trusted databases such as Scopus published in the last 5-10 years. The results of the review showed that exercise using trampolines provides significant benefits in improving physical functions, such as balance, mobility, muscle strength, and cardiopulmonary function, especially in children, the elderly, and groups with special needs such as children with Down Syndrome. In addition, trampolines also play a role in athlete performance optimization and injury prevention through improved proprioception and reduced muscle asymmetry. However, the effectiveness of trampoline training largely depends on the application of proper technique and professional supervision to reduce the risk of injury. In conclusion, trampolines are safe, effective and inclusive exercise tools for a wide range of age groups and physical conditions, with great potential for use in fitness, rehabilitation and sports performance development programs.